2023
DOI: 10.3390/nu15122778
|View full text |Cite
|
Sign up to set email alerts
|

From Listing to Recovery: A Review of Nutritional Status Assessment and Management in Liver Transplant Patients

Abstract: Liver transplantation (LT) is a complex surgical procedure requiring thorough pre- and post-operative planning and care. The nutritional status of the patient before, during, and after LT is crucial to surgical success and long-term prognosis. This review aims to assess nutritional status assessment and management before, during, and after LT, with a focus on patients who have undergone bariatric surgery. We performed a comprehensive topic search on MEDLINE, Ovid, In-Process, Cochrane Library, EMBASE, and PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 230 publications
0
6
0
Order By: Relevance
“…A review has shown that administering 1.2–1.5 times the basal energy expenditure of patients before liver transplantation improves postoperative outcomes for patients undergoing liver transplantation. 15 Merli et al reported that malnutrition is a risk factor for complications and death after liver transplantation. 16 The study by Hammad et al showed that even with good liver function, preoperative nutritional changes persist long after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…A review has shown that administering 1.2–1.5 times the basal energy expenditure of patients before liver transplantation improves postoperative outcomes for patients undergoing liver transplantation. 15 Merli et al reported that malnutrition is a risk factor for complications and death after liver transplantation. 16 The study by Hammad et al showed that even with good liver function, preoperative nutritional changes persist long after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being physically active, the remaining seventeen subjects were outside of a structured exercise program and received indications for the Mediterranean diet. Specifically, the recommendation was about long-term nutritional support after liver transplantation [ 26 ]. In particular, it was recommended to limit fat intake and consume adequate amounts of lean protein to promote muscle development, in parallel with ensuring an adequate calorie intake to avoid protein utilization as an energy source.…”
Section: Methodsmentioning
confidence: 99%
“…Sarcopenic obesity is a term used to define the co-presence of muscle mass depletion and strength reduction with an excess of visceral adiposity; in this case, sarcopenia can be highly overlooked due to the presence of body weight excess [25]. Obesity and sarcopenic obesity worsen the prognosis of cirrhotic patients [26] and are associated with poor transplant waitlist mortality [27,28]. Given these observations, malnutrition and sarcopenia should be promptly recognised and treated.…”
Section: Impact Of Malnutrition In Patients With Liver Cirrhosismentioning
confidence: 99%